PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, DAN UMUR PERUSAHAAN TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY: PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, DAN UMUR PERUSAHAAN TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY - Ai Desy Indriyani; Willy Sri Yuliandhari (Universitas Widyatama, 2020)
Disclosure for CSR is an action taken by a company in order to contribute to economic sustainability that benefits the company, government and society. CSR Activities Serving the form of sustainability reports, however, many companies are still classified as low in their CSR disclosures and have not yet presented them in the form of a sustainability report (sustainability report).The purpose of this study was to determine the effect of the effect of profitability, company size, and company age simultaneously and partially on non-financial LQ 45 Index companies listed on the Indonesia Stock Exchange in 2015-2018.In this study the population consists of non-financial LQ 45 Index companies. The sample selection technique in this study used purposive sampling and obtained 44 total samples. The data used are obtained from sustainability reports and company annual reports. This study uses panel data regression analysis using Eviews version 9.The results showed that profitability, company size, and company age simultaneously affected CSR disclosure with adjusted R2 of 0.307093. Partial profit has a positive effect, while company size and company age have no effect on CSR disclosure.Based on the research results, it is hoped that the disclosure of social responsibility will increase to get the best from investors and the public. Companies with a high level of profitability are expected to be more concerned with CSR activities and their disclosures in the form of company sustainability reports.